2007
DOI: 10.1002/ccd.21133
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional modeling of double‐stent techniques at the left main coronary artery bifurcation using micro‐focus X‐ray computed tomography

Abstract: Close apposition of the stent to the vessel at the ostium of the LCX is difficult to achieve at the LMCA bifurcation, regardless of which double-stent technique is employed, due to the site's wide bifurcation angle and complex 3D structure. The distribution of plaque and the bifurcation angle should be considered before double-stent deployment, to avoid leaving a gap over significant plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…24 Interestingly, however, recent bench test and clinical studies showed these different techniques to be consistently associated with a risk of malapposition, which in turn had been shown previously to be associated with restenosis or late stent thrombosis. [25][26][27] Dedicated DESs may limit the risk of polymer breakage, improving arterial wall coverage; indeed, the risk of ostial restenosis does seem to be reduced, but these studies need to be confirmed. 20 -22,28 At least, the results of the recent Nordic Bifurcation Study III point the interest to discussion of systematic DES kissing postdilatation in bifurcation lesions (M Niemela, Transcatheter Cardiovascular Therapeutics, unpublished data, 2009).…”
Section: Guérin Et Al Bench Study Of Drug-eluting Stent In Bifurcatiomentioning
confidence: 99%
“…24 Interestingly, however, recent bench test and clinical studies showed these different techniques to be consistently associated with a risk of malapposition, which in turn had been shown previously to be associated with restenosis or late stent thrombosis. [25][26][27] Dedicated DESs may limit the risk of polymer breakage, improving arterial wall coverage; indeed, the risk of ostial restenosis does seem to be reduced, but these studies need to be confirmed. 20 -22,28 At least, the results of the recent Nordic Bifurcation Study III point the interest to discussion of systematic DES kissing postdilatation in bifurcation lesions (M Niemela, Transcatheter Cardiovascular Therapeutics, unpublished data, 2009).…”
Section: Guérin Et Al Bench Study Of Drug-eluting Stent In Bifurcatiomentioning
confidence: 99%
“…We demonstrated that microfocus computed tomography (MFCT) with minimal resolution of 0.06 mm was useful for analyzing complex stenting on a phantom model 11 . Stent deformation and gap formation after two‐stent deployment were clearly observed in the 3D reconstruction view 11 . MFCT also has good resolution in both cross‐sectional and longitudinal views.…”
Section: Introductionmentioning
confidence: 99%
“…Phantom Model The construction of an LM bifurcation model was previously reported 11,12 . In brief, a silicon tube corresponding to the left anterior descending artery (LAD) was glued and oriented vertically while a tube corresponding to the circumflex artery (LCX) was glued in a transverse direction, with a 90‐degree angle between both tubes; a tube corresponding to the LM was glued and oriented at a 135‐degree angle with respect to the other two branches 11,12 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This investigational approach illustrates the realistic configuration of the complex bifurcation stenting techniques with clear visualization using high-resolution invasive imaging (e.g., optical coherence tomography, intravascular ultrasound) or noninvasive imaging (e.g., chargecoupled device camera, endoscopy, scanning electron microscopy, and micro-computed tomography(micro-CT) (56,57). Crossing through a proximal cell results in unapposed struts in front of the carina, reduction of the struts-free side branch ostial area, and suboptimal scaffolding of the side branch ostium (Figure 2)(56,58,65). The images acquired are processed to allow volume rendering, geometry rotation, cut-plane views, and fly-through animations.…”
mentioning
confidence: 99%